Estimation of walking improvement in patients after stroke rehabilitated in hospital with application of dynamometric platform - Kwolek, Andrzej; Drużbicki, Mariusz (European Journal of Clinical and Experimental Medicine, 2005)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Stroke is one of the main death and disability causes at mature population. Rehabilitation of patients after stroke is an active and continuous process and one of its objectives is to reconstruct locomotive functions. The target of the work is to evaluate effects of walk’s improvement under conditions of hospitable rehabilitation and to determine usefulness of applying equiponderant exercises on dynamometric platform with use of biological feedback. Subject to assessment at patients were: walk’s speed and number of steps, lower limbs’ load symmetry rate, and functional efficiency according to Barthel’s scale. All patients obtained an improvement of locomotive skills and efficiency as regards everyday activities.